Application of confocal laser scanning microscopy in dendrochronology - Balzano, Angela (Les (Ljubljana), 2019)
We used the Confocal Laser Scanning Microscope (CLSM) Olympus LEXT OLS5000 for non-destructive observation and image analysis of wood anatomy traits in growth layers of tree species from different climatic zones. In European beech (Fagus sylvatica), where tree rings can generally be recognised, we discuss the changes in tree-ring structure due to adverse effects (insect attacks). Growth layers in Mediterranean Aleppo pine (Pinus halepensis) from south-eastern Spain are not always annual and contain numerous intra-annual density fluctuations (IADFs). Ocote pine (Pinus oocarpa) growing at high elevation in Honduras showed growth layers with clear growth ring boundaries and IADFs. In both pines, CLSM allowed us to recognise and measure tracheid parameters to define density fluctuations. In tropical true mahogany (Swietenia macrophylla) from Venezuela and cedrela (Cedrela odorata) from Costa Rica, we studied the growth layers with variable dimensions of vessels demarcated by marginal axial parenchyma.
Keywords: analiza slike; anatomija lesa; branike; confocal laser scanning microscopy; dendrochronology; dendrokronologija; image analysis; konfokalna laserska vrstična mikroskopija; prirastne plasti; tree-rings; wood anatomy; wood identification